Burma news international’s media framing: Critical discourse analysis on the Rohingya crisis - Agwin Degaf; Arrima Fazza Maulidda; Nur Fitria Anggrisia; Zainur Rofiq; Habiba Al Umami (Studies in English Language and Education, 2026)
The Rohingya crisis, underpinned by systemic discrimination and exclusion in Myanmar, continues to be a salient humanitarian concern. While international media have extensively covered the issue, perspectives from Myanmar-based media remain underexplored. Contributing to media discourse analysis, this study examines Myanmar-based reporting to understand how local narratives align with or differ from international discourses. It analyzes how Burma News International (BNI) constructs the Rohingya issue in articles published between March and July 2023, using van Dijk’s Critical Discourse Analysis (CDA) model across macrostructural, superstructural, and microstructural levels. The findings reveal that BNI constructs the Rohingya crisis through interconnected macrostructural, superstructural, and microstructural elements. At the macrostructural level, BNI consistently highlights themes of systemic persecution, repeated arrests, refugee camp incidents, and humanitarian aid, portraying the Rohingya mainly as victims of structural violence. At the superstructural level, the arrangement of headlines, leads, background details, and conclusions emphasizes urgency and humanitarian concern while providing limited representation of Rohingya voices. At the microstructural level, the repeated use of negatively charged language strengthens narratives of vulnerability, marginalization, and crisis. Hence, future studies should examine a broader range of media sources and platforms to further explore how media shape public understanding, reinforce ideological positions, and influence policy responses to humanitarian crises.